Influencer Review, Price Perception, and Brand Image on Purchase Intention of Somethinc Skincare on TikTok: The Moderating Role of Trust - Lola Kalista; Juniwati Juniwati; Bintoro Bagus Purmono; Ramadania Ramadania; Barkah Barkah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Indonesia is the country with the largest number of TikTok users in the world, making the platform widely used as a digital marketing medium, including in the skincare industry. This study aims to analyze the influence of influencer reviews, price perception, and brand image on purchase intention, with trust as a moderating variable in the relationship between influencer reviews and purchase intention for Somethinc skincare products on TikTok. The study employs a quantitative approach using a survey method involving 200 TikTok users in Indonesia as respondents. Data were collected through an online questionnaire and analyzed using PLS-SEM with SmartPLS 4. The results indicate that influencer reviews, price perception, and brand image have a positive and significant effect on purchase intention. Furthermore, trust is proven to strengthen the influence of influencer reviews on purchase intention. This study provides practical contributions for skincare companies in designing more effective digital marketing strategies through TikTok, particularly in building consumer trust in information sources, managing price perceptions, and strengthening brand image to enhance purchase intention. In addition, the findings are expected to serve as an empirical reference for the development of digital marketing and consumer behavior studies in the skincare industry in Indonesia.